Physical therapy in burn wound healing: Development of clinical prediction rules to identify the efficacy of pulsed electromagnetic therapy - Nagy, Ahmed Mohamed; Elsayeh, Shaimaa Mohamed Ahmed; Bayoumi, Mohamed Bayoumi Ibrahim; Metawee, Shimaa Mohamed; Ahmed, Omnia Saeed Mahmoud; Saafan, Karim Ibrahim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Many studies have demonstrated the effect of pulsed electromagnetic therapy (PEMT) on wound healing. This study aimed to develop a clinical prediction rule (CPR) to assess PEMT’s efficacy in burn healing, potentially enhancing treatment decisions and outcomes. It was a one-group intervention study with 46 patients (21 males, 25 females) aged 20 to 55 years, having partial-thickness burns in the first or second healing stage, and a total burned surface area (TBSA) over 15%. The intervention involved pulsed electromagnetic therapy (Fisioline, Italy) for up to six weeks, with 60-minute sessions at 12 Hz and 12 Gauss, three times per week. The statistical analysis was conducted using the SPSS. The study revealed a significant decline in wound surface area (WSA) post-intervention (p < 0.05). A significant negative relationship was found between wound improvement and both age and total body surface area (TBSA) (p < 0.05), while a significant positive relationship was observed between wound improvement and initial wound size (p < 0.05). No significant relationship was found between wound improvement and wound stage (p > 0.05). The study concluded that pulsed electromagnetic therapy significantly reduces wound surface area. Additionally, age, TBSA, and initial burn wound size are important predictors of the therapy’s efficacy in treating burn wounds.